2010
DOI: 10.3109/01443610903474330
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord prolapse: A 10-year retrospective study in two civil hospitals, North Jordan

Abstract: Umbilical cord prolapse (UCP) is an obstetric emergency. The objective of our study was to determine the frequency of cord prolapse, its aetiological factors and to evaluate fetal prognosis. This was a retrospective review of cord prolapse deliveries in the main two civil hospitals in North Jordan between 1995 and 2005, at Princess Badeea Hospital and at King Abdullah University Hospital (KAUH) in Irbid, North Jordan. There were 146 patients identified with UCP among a total of 64,192 consecutive births. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…6 Murphy pointed out that, 'Despite the high incidence of ominous cardiotocographs, low Apgar scores and acidemia on blood gas analysis, the fetal outcome is not as poor as might be expected', based on a perinatal mortality rate of 9.1% (12/132) and a major neurological handicap rate of 0.8% (1/120) among survivors of UCP. Other studies have reported perinatal mortality rates of 2.7% (4/146), 15 3.9% (3/77), 16 9.6% (68/709) 17 and 12.6%. 18 The risk of cord presentation, including UCP and UCD, increased among 180-250-mL TCBC users, but whether the risk of UCP/UCD among 70-150-mL TCBC users (1.5 per 1000 users) was increased, compared with that in no TCBC users, remains uncertain, although a previous report 7 suggests that the risk of UCP is much lower among no TCBC users (around 0.1 per 1000 Japanese women with vertex presentation at term or near term) than among 70-150-mL TCBC users.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…6 Murphy pointed out that, 'Despite the high incidence of ominous cardiotocographs, low Apgar scores and acidemia on blood gas analysis, the fetal outcome is not as poor as might be expected', based on a perinatal mortality rate of 9.1% (12/132) and a major neurological handicap rate of 0.8% (1/120) among survivors of UCP. Other studies have reported perinatal mortality rates of 2.7% (4/146), 15 3.9% (3/77), 16 9.6% (68/709) 17 and 12.6%. 18 The risk of cord presentation, including UCP and UCD, increased among 180-250-mL TCBC users, but whether the risk of UCP/UCD among 70-150-mL TCBC users (1.5 per 1000 users) was increased, compared with that in no TCBC users, remains uncertain, although a previous report 7 suggests that the risk of UCP is much lower among no TCBC users (around 0.1 per 1000 Japanese women with vertex presentation at term or near term) than among 70-150-mL TCBC users.…”
Section: Discussionmentioning
confidence: 91%
“…Murphy pointed out that, ‘Despite the high incidence of ominous cardiotocographs, low Apgar scores and acidemia on blood gas analysis, the fetal outcome is not as poor as might be expected’, based on a perinatal mortality rate of 9.1% (12/132) and a major neurological handicap rate of 0.8% (1/120) among survivors of UCP. Other studies have reported perinatal mortality rates of 2.7% (4/146), 3.9% (3/77), 9.6% (68/709) and 12.6% …”
Section: Discussionmentioning
confidence: 91%
“…No UCP occurrence was recorded in 77, 83, 94, and 412 cases using 30‐mL Foley catheters, in 1083 cases using 50‐mL Foley catheters, or in 98 cases using 60‐mL Foley catheters; however, because data on the risk of UCP in women undergoing spontaneous labor at or near term with cephalic presentation is limited, available studies concerning the usefulness of TCBC for IOL may be too small to draw conclusions about the risk of UCP, which may be inherent in the use of TCBC. Most previous studies dealing with UCP included women with IOL, preterm birth, breech presentation, and/or multifetal pregnancies, and reported varying incidences of UCP, ranging from 1.4 to 3.8 per 1000 women, and consistently indicated that IOL, breech presentation, preterm birth, and/or multifetal pregnancies are risk factors for UCP . Therefore, the risk of UCP in women undergoing spontaneous labor at or near term with cephalic presentation may be somewhat lower than the reported incidence of 1.4–3.8 per 1000.…”
Section: Discussionmentioning
confidence: 98%
“…Most previous studies dealing with UCP included women with IOL, preterm birth, breech presentation, and/or multifetal pregnancies, and reported varying incidences of UCP, ranging from 1.4 to 3.8 per 1000 women, and consistently indicated that IOL, breech presentation, preterm birth, and/or multifetal pregnancies are risk factors for UCP. 13,[15][16][17][18][19][20][21][22][23] Therefore, the risk of UCP in women undergoing spontaneous labor at or near term with cephalic presentation may be somewhat lower than the reported incidence of 1.4-3.8 per 1000. Therefore, we may need data on the risk of UCP in women undergoing spontaneous labor at or near term with cephalic presentation to confirm whether the use of 30-60 mL TCBC does or does not increase the risk of UCP.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, the authors acknowledge that the time between diagnosis and childbirth is a fundamental prognosis factor. 2,3,7,11 For example, for when the period before birth is more than an hour, mortality exceeds 25%, while in general the authors report a mortality of 5% when the time is less than 30 minutes. 12 The minimum time recorded in our series is 18 minutes while the maximum is 16 h with an average of 2 hours 25 minutes.…”
Section: Discussionmentioning
confidence: 99%